Ligands Exert Biased Activity to Regulate Sigma 1 Receptor Interactions With Cationic TRPA1, TRPV1, and TRPM8 Channels - Cortés-Montero, Elsa; Sánchez-Blázquez, Pilar; Onetti, Yara; Merlos, Manuel; Garzón, Javier (Frontiers in Pharmacology, 2019)
The sigma 1 receptor (σ1R) and the mu-opioid receptor (MOR) regulate the transient receptor potential (TRP) V1 calcium channel. A series of proteins are involved in the cross-regulation between MORs and calcium channels like the glutamate N-methyl-D-aspartate receptor (NMDAR), including the histidine triad nucleotide-binding protein 1 (HINT1), calmodulin (CaM) and the σ1R. Thus, we assessed whether similar mechanisms also apply to the neural TRPA1, TRPV1 and TRPM8. Our results indicate that σ1R and CaM bound directly to cytosolic regions of these TRPs, and this binding increased in the presence of calcium. By contrast, the association of HINT1 with these TRPs was moderately dependent on calcium. The σ1R always competed with CaM for binding to the TRPs, except for its binding to the TRPA1 C-terminal where σ1R binding cooperated with that of CaM. However, σ1R dampened HINT1 binding to the TRPA1 N-terminal. When the effect of σ1R ligands was addressed, the σ1R agonists PRE084 and pregnenolone sulfate enhanced the association of the σ1R with the TRPM8 N-terminal and TRPV1 C-terminal in the presence of physiological calcium, as seen for the σ1R-NMDAR interactions. However, these agonists dampened σ1R binding to the TRPA1 and TRPV1 N-terminal domains, and also to the TRPA1 C-terminal, as seen for σ1R-BiP interactions in the ER. By contrast, the σ1R antagonists progesterone and S1RA reduced the association of σ1R with TRPA1 and TRPV1 C-terminal regions, as seen for the σ1R-NMDAR interactions. Conversely, they enhanced the σ1R interaction with the TRPA1 N-terminal, as seen for σ1R-BiP interactions, whereas they barely affected the association of σ1R with the TRPV1 N-terminal. Thus, depending on the calcium channel and the cytosolic region examined, the σ1R agonists pregnenolone sulfate and PRE084 opposed or collaborated with the σ1R antagonists progesterone and S1RA to disrupt or promote such interactions. Through the use of cloned cytosolic regions of selected TRP calcium channels, we were able to demonstrate that σ1R ligands exhibit biased activity to regulate particular σ1R interactions with other proteins. Since σ1Rs are implicated in essential physiological processes, exploiting such ligand biases may represent a means to develop more selective and efficacious pharmacological interventions.